Broccoli or Sulforaphane: Is It the Source or Dose That Matters? - Yoko Yagishita; Jed W. Fahey; Albena T. Dinkova-Kostova; Thomas W. Kensler (Molecules, 2019)
There is robust epidemiological evidence for the beneficial effects of broccoli consumption on health, many of them clearly mediated by the isothiocyanate sulforaphane. Present in the plant as its precursor, glucoraphanin, sulforaphane is formed through the actions of myrosinase, a β-thioglucosidase present in either the plant tissue or the mammalian microbiome. Since first isolated from broccoli and demonstrated to have cancer chemoprotective properties in rats in the early 1990s, over 3000 publications have described its efficacy in rodent disease models, underlying mechanisms of action or, to date, over 50 clinical trials examining pharmacokinetics, pharmacodynamics and disease mitigation. This review evaluates the current state of knowledge regarding the relationships between formulation (e.g., plants, sprouts, beverages, supplements), bioavailability and efficacy, and the doses of glucoraphanin and/or sulforaphane that have been used in pre-clinical and clinical studies. We pay special attention to the challenges for better integration of animal model and clinical studies, particularly with regard to selection of dose and route of administration. More effort is required to elucidate underlying mechanisms of action and to develop and validate biomarkers of pharmacodynamic action in humans. A sobering lesson is that changes in approach will be required to implement a public health paradigm for dispensing benefit across all spectrums of the global population.